Enhanced recovery after surgery: Narrative review in gynecologic pelvic exenterations - Barger, Abigail; Huepenbecker, Sarah P. (Frontiers in Oncology, 2025)
In this narrative review, we discuss enhanced recovery after surgery (ERAS) in pelvic exenterations from a gynecology oncology perspective. There is limited evidence regarding perioperative guidelines for this complex surgical procedure. We will review ERAS societal guidelines, collaborative reviews, expert opinions and provide tables summarizing the pre-admission, preoperative, intraoperative, and postoperative guidelines provided by these sources. We will look at how ERAS protocols have been used in published studies. Lastly, we discuss potential future directions for perioperative care in pelvic exenterations.